Implementation of Educaplay Media as An Arabic Conversation Learning Innovation - Namiyah Fitriani; Rima Ayu Handayani; Putri Fatimah Azzahrah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the implementation of the Educaplay platform as an innovative medium in learning Arabic conversation in the pesantren environment, focusing on its effectiveness, challenges, and impact on the learning motivation of students of the Madinatul Ulum Mumbang Islamic Boarding School. The research method uses a descriptive qualitative approach by collecting data through interviews with three respondents and documentation. The data were analyzed following the Miles and Huberman model (data reduction, data presentation, and conclusion verification). The results showed that Educaplay was successful in improving learning interactivity through the Dialogue Game feature, which facilitates self-paced conversation practice with instant feedback on pronunciation, grammar, and speaking fluency. The implementation of this platform reduced learning boredom and strengthened vocabulary mastery, although significant variation was found in learning outcomes between students (completion time: 2–9 minutes; errors: 5–47). The conclusion of the study confirms that Educaplay is effective as a complement to innovation methods in Islamic boarding schools, provided that there is teacher training and supporting infrastructure. These findings recommend the integration of game-based learning-based technology in the Arabic curriculum, while highlighting the need for pesantren policies to address the digital divide.